Malignant peripheral nerve sheath tumor of the bladder - A case report - Petracco, G.; Patriarca, C.; Spasciani, R.; Parafioriti, A. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Malignant peripheral nerve sheath tumor (MPNST) is an uncommon malignant tumor often associated with Neurofibromatosis type 1 (NF1). Although different soft tissue mesenchymal tumors may arise in the bladder, MPNST is a very rare occurrence. Here, we present a case of MPNST of the bladder in a 50 year old patient with NF1 with involvement of the entire wall of the organ leading to a functional exclusion. The principal differential diagnoses and a short review of the literature are presented.